Library Promotion in State Islamic Institute of Padang Sidimpuan - Nasution, Cindy Fadilah; Siregar, Yusra Dewi (Pena Cendekia Insani, 2022)
This study discusses the Promotion Strategy at the UPT Library of the State Islamic Institute (IAIN) Padangsidimpuan. This research method uses a qualitative descriptive approach. By using data collection techniques through interviews, observation and documentation. The informants in this study were the head of the library and the librarian at the Padangsidimpuan State Islamic Institute Library (IAIN) who had been selected by according to researchers to the criteria of the research subject. The results of the study indicate that the library's strategy is to promote the Padangsidimpuan library (IAIN) on social media created by the library by creating a website so that users who access it get information about the Padangsidimpuan library (IAIN). Promotion through other social media with Facebook, Instagram and library promotion activities that contain updated information about the Padangsidimpuan library (IAIN). The library also carries out various activities to promote the Padangsidimpuan library (IAIN) such as webinars, user education and competitions organized by the Padangsidimpuan library (IAIN)